Effect Fresh Milk on Surface Roughness of Resin Modified Glass Ionomer Cement: Efek Susu Segar Terhadap Kekasaran Permukaan Semen Ionomer Kaca Modifikasi Resin - Yudhit, Astrid; Harahap, Kholidina Imanda; Dewi, Yuli Ratna (TALENTA, 2019)
Resin modified glass ionomer cement as restorative material used in dentistry especially in primary teeth. Fresh milk is often consumed by children as daily drink and it contains lactic acid. The aim of this study was to evaluate surface roughness of resin modified glass ionomer cement after immersed in fresh milk for 2, 4, and 6 hours. Samples were disc shape resin modified glass ionomer cement with size 5 mm in diameter and 2 mm in thickness. Totally 24 samples were divided into 3 groups (n=8), group immersed for 2 hours, group immersed for 4 hours, and group immersed for 6 hours. Fresh milk was pure cow’s milk that harvest in the morning by the farmer. Surface roughness measurements was done before and after immersed using a profilometer (Surfcorder SE-300, Laboratory Ltd, Japan). Results showed surface roughness change were 0.0217 ± 0.005 μm for groups A, 0.0366 ± 0.006 μm for groups B, and 0.0555 ± 0.004μm for groups of 6 hours. One Way Anova test showed significant differences between groups (p <0.05). It can be concluded that there was significant increased on surface roughness of modified resin ionomer cement after immersed in fresh milk for 2, 4 and 6 hours.